C5a alters blood–brain barrier integrity in a human in vitro model of systemic lupus erythematosus. Issue 1 (15th July 2015) - Mahajan, Supriya D.; Parikh, Neil U.; Woodruff, Trent M.; Jarvis, James N.; Lopez, Molly; Hennon, Teresa; Cunningham, Patrick; Quigg, Richard J.; Schwartz, Stanley A.; Alexander, Jessy J.
Summary The blood–brain barrier (BBB) plays a crucial role in brain homeostasis, thereby maintaining the brain environment precise for optimal neuronal function. Its dysfunction is an intriguing complication of systemic lupus erythematosus (SLE). SLE is a systemic autoimmune disorder where neurological complications occur in 5–50% of cases and is associated with impaired BBB integrity. Complement activation occurs in SLE and is an important part of the clinical profile. Our earlier studies demonstrated that C5a generated by complement activation caused the loss of brain endothelial layer integrity in rodents. The goal of the current study was to determine the translational potential of these studies to a human system. To assess this, we used a two dimensional in vitro BBB model constructed using primary human brain microvascular endothelial cells and astroglial cells, which closely emulates the in vivo BBB allowing the assessment of BBB integrity. Increased permeability monitored by changes in transendothelial electrical resistance and cytoskeletal remodelling caused by actin fiber rearrangement were observed when the cells were exposed to lupus serum and C5a, similar to the observations in mice. In addition, our data show that C5a/C5aR1 signalling alters nuclear factor‐κB translocation into nucleus and regulates the expression of the tight junction proteins, claudin‐5 and zonula occludens 1 in this setting. Our results demonstrate for the first time that C5a regulates BBB integrity in a neuroinflammatory setting where it affects both endothelial and astroglial cells. In addition, we also demonstrate that our previous findings in a mouse model, were emulated in human cells in vitro, bringing the studies one step closer to understanding the translational potential of C5a/C5aR1 blockade as a promising therapeutic strategy in SLE and other neurodegenerative diseases.